PENANAMAN NILAI-NILAI KEASWAJAAN PARA KADER PMII DI UIN MAULANA MALIK IBRAHIM MALANG - Ulya, Solihatul; Albadri, Abdun Nashir; Masyhuri, Masyhuri (JURNAL ISLAM NUSANTARA, 2021)
Currently, there are various issues related to religion which have become a serious topic to be discussed. As an organization that makes Ahlus Sunnah Wal Jama'ah (ASWAJA) as the Basic Value of the Movement (NDP), PMII certainly has an important role in producing young mujtahid cadres who are able to respond to the reality they face by maintaining the spirit of aswaja. This study aims to describe the instillation of aswaja values on cadres at PMII UIN Maulana Malik Ibrahim. The moral values that are instilled in the PMII organization are the values of tasamuh, tawasuth, tawazun, and ta'adul. The research method used is descriptive qualitative. Based on the results of the research analysis, it can be concluded that the implementation of aswaja values has been applied by high-ranking PMII UIN Maulana Malik Ibrahim Malang to its members. This pattern of inculcating or implementing the values of self-reliance is elaborated through PMII's main activities such as in routine studies and discussion forums.